Hubungan Dukungan Emosional Keluarga dengan Tingkat Stres pada Pasien Diabetes Melitus Tipe 2 di Wilayah Kerja Puskesmas Bulango Selatan - Mamu, Indrawati; Zainuddin, Zainuddin; R. Yusuf, Nur Ayun; Yulian Hunowu, Sri (Mando Care Jurnal, 2025)
Type 2 Diabetes Mellitus is a chronic disease with a globally increasing prevalence and can lead to stress in sufferers. High levels of stress can affect blood glucose control and increase the risk of complications. Family emotional support plays an important role in helping patients manage stress and improve their quality of life. This study is a quantitative research with a cross-sectional approach, consisting of an independent variable of family emotional support and a dependent variable of stress level. The population in this study consisted of 58 respondents, with purposive sampling yielding 51 respondents. The instruments used in this study were a family emotional support questionnaire and the Perceived Stress Scale (PSS-10). Data analysis was conducted using Spearman rank correlation. The analysis results show a significant negative relationship between family emotional support and the stress level of patients, with a p-value of 0.000 (p < 0.05) and a correlation coefficient (rho) of -0.503. This indicates that the higher the emotional support from the family, the lower the stress level experienced by the patient, and vice versa.